A importância das informações aferentes podais para o controle postural - de Camargo, Marcela Regina [UNESP]; Fregonesi, Cristina Elena Prado Teles [UNESP] (My University, 2011)
Introduction. The postural control involves a complex mechanism for connecting the afferent and efferent pathways and their integration into the central nervous system (CNS). Three systems are responsible to obtain outside information: visual, vestibular and sensory. Recent studies have shown that among such systems, the CNS shows a greater predilection for sensory information to postural control. Objective. Given this, the review proposes to discuss the feet sensory information importance and its reflection in postural control mechanisms. Method. For this reason, a literature search was carried out by PubMed and Bireme libraries, and papers of the last five years were selected. Specific books were also used. Discussion. Studies were separated into topics on sensory information integration to neuro-motor answer, postural feed-forward adjustments recruitment mechanisms; neuro-muscular coordination and synergy responses and the musculoskeletal tissues role. Conclusion. Despite has been found a large number of studies, the real mechanism that the CNS uses to filter, integrate and process the sensory information and select the appropriate motor response, be it for the movement or posture for the stabilization remains obscure.
Feet afferent information importance to postural control
Keywords: Foot; Posture; Proprioception; Sensation; body equilibrium; body posture; feet sensory information; library; Medline; proprioception; sensory nerve conduction